A Study on the Interfacial Structure Design of Self‐Compliance Ni/HfOx/Ni Bipolar Selectors and Trap‐to‐Trap Tunneling Mechanism Caused by Redox Reaction. Issue 5 (30th December 2019) - Wang, Liyuan; Cao, Lili; Miao, Min; Zhang, Hao; Luo, Bingwei
Abstract : Selectors are considered some of the most significant devices applied to the integration of resistive random access memory (RRAM). Self‐compliance selectors promote the stability of one selector and one resistor (1S1R) cell to reduce additional compliance current circuits without compromising RRAM switching performance. Herein, a Ni/HfO x /Ni bipolar selector with special cluster microstructures is fabricated via a facial magnetron sputtering technology, which has self‐compliance (±12 μA) performance and ultrahigh voltage endurance (±10 V). To investigate the mechanism, theoretical models for the self‐compliance selectors are proposed. The results demonstrate that traps and special interfaces are formed through redox reactions. Resistive switching properties are caused by the trap‐to‐trap tunneling structure of the HfO x –NiO y layers. At the interfaces of HfO x –NiO y oxide layers, the tunneling current reaches a saturation state, leading to the self‐compliance phenomenon, which provides a theoretical and research foundation for the development of RRAM technology. Abstract : A Ni/HfO x /Ni bipolar selector is fabricated via a facial method. Special cluster microstructures and interfacial effects are obtained. As a result, the selector exhibits self‐compliance and ultrahigh endurance characteristics. Moreover, the operational oxygen migration mechanism of selectors is analyzed. Its properties are caused by trap‐to‐trap tunneling structure of HfO x –NiO y layers.